Digital Transformation of BPJS Primary Healthcare Administration: A Qualitative Study of E-Module Implementation and Service Quality Improvement - Benri Situmorang; Aris Citra Wisuda; Herlina Herlina; Febriantika Febriantika (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Indonesia’s National Health Insurance system (BPJS Kesehatan) continues to face persistent administrative challenges in primary healthcare, including limited accessibility, bureaucratic complexity, long waiting times, and patient dissatisfaction. To address these issues, digital transformation initiatives have introduced electronic modules (e-modules) aimed at improving administrative efficiency, service quality, and data accuracy. This qualitative study collected data through in-depth interviews with twenty participants: twelve BPJS beneficiaries and eight primary healthcare officers from four community health centers in Sibolga City, North Sumatra. Participants were purposively selected based on their experience with BPJS e-module services. Interviews were transcribed verbatim and analyzed thematically using NVivo 12 through open coding, categorization, and theme development. Four themes emerged: 1) Administrative accessibility improved as e-modules simplified access to procedural information; 2) Service efficiency increased through shorter waiting times and faster processing; 3) User satisfaction improved, especially among digitally literate participants who perceived greater transparency and predictability, and 4) Administrative accuracy strengthened due to standardized digital documentation, reducing manual errors. Nonetheless, barriers persisted, including limited digital literacy, uneven internet connectivity, and insufficient technical support at facility level. E-modules represent an effective administrative innovation that reduces procedural complexity and enhances service consistency in primary healthcare. However, uneven benefits resulting from infrastructural constraints, organizational inertia, and varying user capacity underscore the need to align technological implementation with institutional readiness and user support to prevent widening service disparities Keywords: BPJS Health, Primary Healthcare, E-Module, Digital Health Administration, Service Quality